Observation of the application effect of low-volume polyethylene glycol electrolyte lavage solution (PEG-ELS) combined with ascorbic acid tablets in bowel preparation for colonoscopy in hospitalized patients - Wu, Le-Can; Zheng, En-Dian; Sun, Hao-Yue; Lin, Xi-Zhou; Pan, Ju-Yi; Lin, Xiao-Xiao (Frontiers in Oncology, 2023)
Background: This study explored the effectiveness and safety of low-volume polyethylene glycol electrolyte lavage solution (PEG-ELS) combined with ascorbic acid tablets (PEG-ELS/Asc) in bowel preparation for a colonoscopy. Methods: A total of 240 hospitalized patients who underwent a colonoscopy in Wenzhou People’s Hospital, Wenzhou Third Clinical College of Wenzhou Medical University from July 2020 to June 2022 were randomly divided into two groups, with 120 patients each. All of the participants were given a low-residue or residue-free diet one day before the examination and fasted after dinner (completed before 18:00) the day before the examination. The 2-L PEG-ELS/Asc group took 2-L PEG-ELS plus 10 g ascorbic acid tablets once orally, while the 3-L PEG-ELS group took 3-L PEG orally on several occasions. The primary endpoint was the achievement of preparation adequacy and an overall colon cleansing score of ≥6, both assessed by blinded investigators using the Boston Bowel Preparation Scale (BBPS). The bowel cleansing effect, polyp detection rate, adverse reaction rate, oral drug tolerance rate, renal function, and electrolyte level changes were also compared between the two patient groups. Results: There were no significant differences in the success rate of bowel preparation, the detection rate of polyps, or the adverse reaction rate between the two groups (P > 0.05). The tolerance rate of bowel preparation in the 2-L PEG-ELS/Asc group was significantly higher than that in the 3-L PEG-ELS group (93.3% vs. 80.23%) (P < 0.05). The levels of creatinine, serum potassium, serum sodium, and serum chlorine of the two groups before and after bowel preparation were within the normal range. In addition, the intestinal cleaning effect of the two preparation schemes for the hospitalized patients with diabetes and constipation is worse than that of those without these conditions (P < 0.05). Conclusion: The effectiveness and safety of using 2-L PEG-ELS/Asc in bowel preparation for a colonoscopy in hospitalized patients were not inferior to using 3-L PEG-ELS. For patients with diabetes and constipation, the cleansing effect of the two bowel preparation options was not very satisfactory, and further clinical research is needed in this regard.